Cottage industries in Kelantan / Nor Hamidah Abdullah… [et al.] - Abdullah, Noor Hamidah; Talip, Normah; Abdullah, Ahmad Shuyuti; Ali, Mohd. Hasni; Yusof, Mahani Mohd.; Basman, Said; Mahmood, Naterah; Saimin, Awang Ismail; Tg. Ismail, Tg. Nawawi; Ibrahim, Hishamuddin (1976)
This paper is purely an academic exercise to fulfill an academic requirement for the subject, Development Administration, and it should not be seen beyond this. The topic "Cottage Industries in Kelantan" is especially chosen because of its unique characteristics in certain aspects. The great pace of science and technology has not deeply found its way ( or should we say none) in those Cottage Industries. They still retain their unique identities and the paving away of those, will merely mean a destruction of the traditional handicraft practised for generations. Furthermore, very few studies had been made in various aspects of Cottage Industires in Kelantan, Therefore, we fully hope that our study would help to contribute in as many ways as possible| if not much, towards any study of the above topic which would be made by others from time to time.